Manfaat Kesehatan Tanaman Pala (Myristica fragrans) (Health Benefits of Nutmeg (Myristica fragrans )) - Lisna Rosalia Agaus; Reski Vinalia Agaus (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2019)
ABSTRACTIntroduction: Myristica fragrans has its origins in the Spice Islands of Indonesia, formerly known as the spice islands. Fragrant rich nutmeg is one of the highly prized spices known since antiquity for its aromatic, aphrodisiac, and curative properties. Since ancient times, nutmeg has been used as a remedyfor various ailments or to improve health in general.  Purpose: Although the culinary value of this magical spice is well-known, its medicinal and therapeutic values are mostly unheard of. So that, the purpose of this research is to clarify the health benefits of nut meg.                       Methode: This research is an descriptive research. Result:  Health benefits nutmeg is used as a stomachic, stimulant, carminative as well as for intestinal catarrh and colic, headaches, diarrhea, vomiting, nausea, fever, bad breath, to stimulate appetites and to control flatulence.  It is also valuable for its aphrodisiac and antiinflammatory properties. Studies show that it can help lower blood pressure and sooth a stomach ache as well as stop diarrhea and (in low dose) help to detoxify the body, stimulate the brain.Conclusion: Nut meg have many health benefits so nut meg must be processed to be a good herbal product which is easilya acessible to the public. Keywords: Health benefits, nutmeg